Analysis of GPS visibility and satellite-receiver geometry over different latitudinal regions - Yahya, Mohd. Hafiz; Kamaruddin, Md. Nor (2008)
GPS is the only fully-operational GNSS currently available to all-inclusive users at no direct charge. Given that users obtain their positions by receiving radiowave signals transmitted from its continuously orbiting satellites, proper functioning of a GPS receiver requires uninterrupted signal reception from at least four orbiting satellites with good satellite-receiver geometry. This paper investigates the variation of satellite visibility and satellite-receiver geometry over three latitudinal regions. To signify the corresponding high latitude region, mid latitude region and equatorial region, three reference stations namely IRKT, XIAN and NTUS were selected. Based on series of satellite almanac data, it is suggested that local sky coverage varies as a function of the tracking station latitude. Throughout the observation period, it is noted that equatorial region provides the most number of satellites in comparison to the mid latitude and the high latitude region. As far as satellitereceiver geometry is concern, equatorial region tends to produce the best DOP hence more likely to produce better result in GPS positioning in comparison to the other regions. As the satellite-receiver geometry changes with time due to the relative motion of the orbiting satellites, it is suggested that DOP value is inversely proportional to the number of observed satellites. It is detected that DOP value also increases with increases in the elevation angle.